The identity of Coolia-toxin producing species - Mohammad Noor, Normawaty; Moestrup, Ojvind; Lundholm, Nina; Fraga, Santiago; Holmes, Michael J. (2013)
In the literature, c. monotis was reported in 1995 to produce cooliatoxin, but subsequent studies have shown that identification of the species is likely to be incorrect. The present study was conducted to clarify which species was responsible for cooliatoxin production by re-examination of the material used in the report of cooliatoxin and of other cultures of C. tropicalis collected from different sites including the type locality. LSU rDNA was carried out to support the morphological results. Based on morphological description of C. tropicalis is emended- A phylogenetic analysis supported the contention that C. tropicalis is a distinct species within the genus Coolia' The identity of the species responsible for cooliatoxin production was finally revealed. The study clarifies some of the taxonomic problem, related to benthic dinoflagellates, particularly the genus Coolia'